2023
DOI: 10.1186/s12891-023-06634-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mean incidence and variance of orthopedic diseases before and during the COVID-19 pandemic in Korea: a retrospective study

Abstract: Background During the coronavirus disease (COVID-19) pandemic, the amount of moderate- to high-intensity physical activity significantly decreased. Therefore, the epidemiology of musculoskeletal diseases could possibly have changed. We assessed changes in the incidence of and variance in non-traumatic orthopedic diseases before and after the COVID-19 pandemic in Korea. Methods This study included data from the Korea National Health Insurance Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that diabetes may be an independent risk factor for frozen shoulder[ 28 ]. Diabetes is a metabolic disease that has been confirmed to be associated with a variety of systemic diseases and pain symptoms \* MERGEFORMAT [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that diabetes may be an independent risk factor for frozen shoulder[ 28 ]. Diabetes is a metabolic disease that has been confirmed to be associated with a variety of systemic diseases and pain symptoms \* MERGEFORMAT [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pandemic has imposed delays on elective surgeries, emergency surgeries were performed as needed. It has been shown that the number of elective surgeries has significantly decreased during the pandemic, while trauma and emergency surgeries have not decreased [ 16 ]. Since surgical treatments for fractures are more often required in younger patients, the number of surgeries has decreased less in children [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other is the time range of the data collected. The reduced volume of orthopedic surgeries due to the COVID-19 pandemic has gradually recovered over time [ 16 ]. As the data collected in the earlier studies reflect shorter periods at the beginning of the pandemic, the decrease in the number of surgical treatments might have been exaggerated when compared to later studies, which include the “recovery” period of operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation